Maternal mortality from 1958 to 1996. Experience in the National Edgardo Rebagliati Martins Hospital - 38 years - Pacheco, José (2015)
To examine the tendency of maternal mortality at one National Hospital of the Social Security Peruvian Institute. DESIGN: Epidemioloqic descriptive retrospective study of maternal deaths registered at our Hospital. SUBJECTS: 202 women that died during Pregnancy, delivery or postpartum, LOCATION: Department of Obstetrics and gynecology of Edgardo Rebagliati Martins National Hospital, SSPI. RESULTS: Direct obstetrical deaths represented 73,3% (1 48 cases), including 26,2% (53 cases) of pregnancy induced hypertension, 24,8% (50 cases) of infections, 14,9% (30 cases) of hemorrhage and 7,4% (15 cases) of other direct obstetrical causes. Indirect maternal death causes were 26,2% (53 cases) and non related 0,5% (1 case). Maternal mortality rate was 40,3/100000 l.n.b. CONCLUSIONS: Emphasis is placed on the importance of the study of maternal deaths, most of them preventable, so as to contribute to their reduction. We also mention institutional problems that repercute in maternal mortality rates.